2014
DOI: 10.1590/s0103-90162014000100008
|View full text |Cite
|
Sign up to set email alerts
|

Do soil fertilization and forest canopy foliage affect the growth and photosynthesis of Amazonian saplings?

Abstract: Most Amazonian soils are highly weathered and poor in nutrients. Therefore, photosynthesis and plant growth should positively respond to the addition of mineral nutrients. Surprisingly, no study has been carried out in situ in the central Amazon to address this issue for juvenile trees. The objective of this study was to determine how photosynthetic rates and growth of tree saplings respond to the addition of mineral nutrients, to the variation in leaf area index of the forest canopy, and to changes in soil wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 50 publications
3
19
0
4
Order By: Relevance
“…Values of Q und reported in this study are similar to those found in previous studies in the same area (Marenco & Vieira, 2005;Magalhães et. al.…”
Section: The Physical Environmentsupporting
confidence: 92%
See 3 more Smart Citations
“…Values of Q und reported in this study are similar to those found in previous studies in the same area (Marenco & Vieira, 2005;Magalhães et. al.…”
Section: The Physical Environmentsupporting
confidence: 92%
“…The high N/P ratio (Koerselman & Meuleman, 1996) and the low leaf P content found in sapling leaves supports the belief that in the old and highly weathered Amazonian soils, P can limit tree growth in this ecosystem (Reich & Oleskyn, 2004). Nevertheless, Magalhães et al (2014) failed to detect any significant plant response to the addition of P, which suggests that the amount of P they added was not sufficient to cause any detectable effect on plant functioning; it is well known, for example, that oxisols have a high capacity for P fixation. Wright et al (2011) reported that the addition of P only marginally enhanced seedling growth rates in a lowland tropical forest of Panama.…”
Section: Leaf Nutrient Contentmentioning
confidence: 59%
See 2 more Smart Citations
“…A taxa máxima de transporte de elétrons (J max ) e V cmax (valores padronizados a 25°C) variam consideravelmente entre espécies. V cmax varia na faixa de 10 a 75 µmol m -2 s -1 (Domingues et al, 2014;Magalhães et al, 2014) e J max varia entre e 40 e 112 µmol m -2 s -1 (Domingues et al, 2007;Magalhães et al, 2014), estando ambos parâmetros altamente correlacionados. A relação J max / V cmax varia de 1 a 1,67 (Medlyn et al, 2002).…”
Section: Fotorrespiraçãounclassified